Scandinavian studies - Society for the Advancement of Scandinavian Study (U.S.) (Society for the Advancement of Scandinavian Study, 1941)
Includes proceedings of the society.
Keywords: Scandinavian philology : Periodicals; Scandinavian languages : Periodicals; Philologie scandinave : Périodiques; Langues scandinaves : Périodiques; Scandinavian languages; Scandinavian philology